Comparison of protein, total fat, and omega-3 fatty acids content in yellowtail catfish (Pangasius pangasius) and long tail shad (Hilsa (clupea) macrura) in raw and pressurized fish - Rahmat, Asmah; Raja Shaikh Alauddin, Siti Sumaiyah; Ramli, Nurul Shazini (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Omega-3 fatty acids have been shown to reduce the risk of chronic diseases like cardiovascular disease and cancer as well as promote brain development among infants and children. This study was carried out to compare total protein, fat and omega-3 fatty acids content of raw and pressurized fish of P. pangasius (yellowtail catfish) and H. macrura (long tail shad). The fish was cooked using pressure cooker for six minute to be pressurized. The protein content was determined by using Kjedahl method while total fat was determined using solvent extraction using chloroform and methanol. Fatty acid methyl esters (FAME) were prepared by a direct transesterification method, and quantified by gas chromatography using external standard. Results showed that marine fish H. macrura (long tail shad) had higher content (p < 0.05) of protein (18.30 ± 0.040 g/100 g), fat (10.965 ± 1.610 g/100 g), EPA (11.83 ± 0.02 g/100 g) and DHA (5.96 ± 0.31 g/100 g) compared to freshwater fish P. pangasius (yellowtail catfish). The protein content of pressurized fish was higher compare to raw fish, but there was no difference in total fat and omega-3 fatty acids content between raw and pressurized of freshwater fish P. pangasius and marine fish, H. macrura. In conclusion, marine fish are better source of protein, fat and omega-3 content, while pressurized fish shown to have comparable amount of protein, fat and omega-3 fatty acids content with raw fish. The result obtained assist the consumers to prepare a healthy menu in order to retain the protein and omega-3 fatty acids content of fish through healthy way of cooking.